Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/cpmo.21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mtDNA/nDNA Ratio in Mice

Abstract: The mitochondrial DNA (mtDNA) lacks a protection provided by the nucleosomes in the nuclear DNA and does not have a DNA repair mechanism, making it highly susceptible to damage, which can lead to mtDNA depletion. MtDNA depletion compromises the efficient function of cells and tissues and thus impacts negatively on health. Here, we describe a brief and easy protocol to quantify mtDNA copy number by determining the mtDNA/nDNA ratio that we validated in a cohort of young and aged mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
211
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(213 citation statements)
references
References 17 publications
1
211
1
Order By: Relevance
“…These data also add to the current understanding of PolG model in the context of aging more generally. Previous studies found that mtDNA copy number decreases with age [5,32]. Our results showed slightly decreased mtDNA copy number with age in wild-type mice, though it was not statistically significant.…”
Section: Copy Number Effectscontrasting
confidence: 80%
“…These data also add to the current understanding of PolG model in the context of aging more generally. Previous studies found that mtDNA copy number decreases with age [5,32]. Our results showed slightly decreased mtDNA copy number with age in wild-type mice, though it was not statistically significant.…”
Section: Copy Number Effectscontrasting
confidence: 80%
“…The copy number of mitochondrial gene ND1 was normalized to the single-copy nuclear gene. Relative mtDNA copy number was calculated and expressed by using the 2− ∆∆CT method [44].…”
Section: Quantification Of Mtdna Copy Numbermentioning
confidence: 99%
“…These data also add to the current understanding of PolG mice in particular. Previous studies found that mtDNA copy number decreases with age (5,30). Our results showed slightly decreased mtDNA copy number with age, though it was not statistically significant.…”
Section: Discussionmentioning
confidence: 93%